2004
DOI: 10.5713/ajas.2004.1518
|View full text |Cite
|
Sign up to set email alerts
|

Study on Nutritive Value of Tropical Forages in North Sumatra, Indonesia

Abstract: MATERIALS AND METHODS Experimental siteThis study was conducted in Medan (North Sumatra), Indonesia. The province is located in the tropical and monsoon region, and lies between 98-100° East and 1-4° N. There are two seasons during the year, dry season from February to September and rainy season from November to March. The temperature is nearly constant, differing by only a few degrees among the dry and rainy seasons with daily temperature ranges from 18 to 34°C. The annual rainfall ranges from 1,100 to 3,400 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
19
3
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 20 publications
(22 reference statements)
8
19
3
4
Order By: Relevance
“…It has been observed that the legume/browse species contained higher crude protein content than in the grass species. Similar findings were made in the works of Evitayani et al (2004), Babayemi (2007), Ajayi and Babayemi (2008) and Asaolu et al (2014). Also, the crude protein contents of the legume/browse species in the current study were well above the minimum requirement of 11.0 to 13.0% recommended for maintenance and moderate growth of goats (Poppi and McLennan, 1995).…”
Section: 12supporting
confidence: 75%
See 1 more Smart Citation
“…It has been observed that the legume/browse species contained higher crude protein content than in the grass species. Similar findings were made in the works of Evitayani et al (2004), Babayemi (2007), Ajayi and Babayemi (2008) and Asaolu et al (2014). Also, the crude protein contents of the legume/browse species in the current study were well above the minimum requirement of 11.0 to 13.0% recommended for maintenance and moderate growth of goats (Poppi and McLennan, 1995).…”
Section: 12supporting
confidence: 75%
“…Thus Ajayi and Babayemi (2008) found out that there were increased proximate composition and in vitro gas production values in the grass/ legume mixtures than sole grass. Other earlier researchers, Evitayani et al (2004) studied the nutritive values of tropical forages commonly used as ruminant feeds in North Sumatra, Indonesia. They observed that crude protein content ranged from 6.6 to 16.2% in grass and from 17.5 to 29.1% in legumes.…”
Section: Introductionmentioning
confidence: 99%
“…These study also showed that CP content of both legumes planted in peatland was generally lower than those found by several researches. Evitayani et al (2004), Omele et al (2011) and Martens et al (2012) reported that CP content of C. pubescen was 18.9%, 25.5%, and 23.6%, respectively. However, Mahala et al (2012), Nasrullah et al (2003) and Heinritz et al (2012) reported that CP content of C. ternatea was 17%, 18.28%, and 19%, respectively.…”
Section: Stylosanthes Guianensis)mentioning
confidence: 99%
“…Heuzé & Tran (2012) reported that NDF content of S. splendida was 69.5%. Evitayani et al (2004) reported that NDF content of C. pubescens that grows in North Sumatra was 51.1%. Nasrullah et al (2003) found that NDF content of C. ternatea which grows naturally in South Sulawesi was 42.30%.…”
Section: Stylosanthes Guianensis)mentioning
confidence: 99%
See 1 more Smart Citation